Effects of aquatic exercise compared with land-based exercise on the body composition and function of older adults with sarcopenia: protocol for a randomised controlled trial - Na Li; Fang Cheng; Jinfeng Yang; Yuanpeng Liao; PeiJie Sun; Weicheng Yang; Jinqi Yang; Jianxin Ran (BMJ Open)
Introduction Sarcopenia is a condition that occurs more frequently in older adults. Although many types of exercise have been used in the treatment of sarcopenia, few studies have been conducted on different interventional environments for sarcopenia. The purpose of this study is to investigate the effects of aquatic exercise and land-based exercise on the body composition and function of participants with sarcopenia.Methods and analysis This randomised, controlled, single-blinded trial will enrol 45 participants (≥ 65 years) following the diagnostic criteria set by the Asian Working Group for Sarcopenia 2019. Participants will be randomised and assigned to one of three groups (aquatic exercise group, land-based exercise group and control group). Assessments will be conducted four times: initially (before intervention), after 8 weeks (intermediate), after 16 weeks (final) and 16 weeks after the end of intervention (follow-up). The primary outcomes are appendicular skeletal muscle index and handgrip strength, while the secondary outcomes include the Short Physical Performance Battery, 6-minute walk test and the Chinese version of the 36-item short-form of health-related quality of life.Ethics and dissemination Ethics approval was obtained from the Ethics Committee of Chengdu Sport University, with permission number CDSUEC2023-125. This study has been registered with the Chinese Clinical Trial Registry (ChiCTR2300077457). All participants will provide written informed consent.Trial registration number Chinese Clinical Trial Registry ChiCTR2300077457.